2018
DOI: 10.1159/000488457
|View full text |Cite
|
Sign up to set email alerts
|

Acral Lentiginous Melanoma Is Associated with Certain Poor Prognostic Histopathological Factors but May Not be Correlated with Nodal Involvement, Recurrence, and a Worse Survival

Abstract: Background/Aims: Acral lentiginous melanoma (ALM) is a small subtype of melanoma affecting Caucasians far more often than other ethnic groups, such as blacks, Hispanics, and Asians. Only a few studies have yielded controversial results on ALM so far. The aim of this study was to define the histopathological and clinical expressions of ALM and to compare them with those of non-ALM in a large group of Turkish patients from a single referral institution. Methods: One hundred two ALM patients were analyzed retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 8 publications
4
22
0
Order By: Relevance
“…Another study, 10 however, showed that the proportion of stage III/IV in the palm group was threefold higher than that in the nail bed group, which may be due to race variation. The overall distant metastases percentage in our study was comparable with previous literature 2 , 18 but the sole population had a higher proportion of distant metastases. No statistical difference was found for metastases of lung, liver, brain, bone, or non-regional lymph nodes across the 3 acral subgroups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another study, 10 however, showed that the proportion of stage III/IV in the palm group was threefold higher than that in the nail bed group, which may be due to race variation. The overall distant metastases percentage in our study was comparable with previous literature 2 , 18 but the sole population had a higher proportion of distant metastases. No statistical difference was found for metastases of lung, liver, brain, bone, or non-regional lymph nodes across the 3 acral subgroups.…”
Section: Discussionsupporting
confidence: 91%
“…These are in keeping with Bradford et al's 3 and another 3 reports. 11,18,19 Meanwhile, previous studies 11,20,21 reported that more physical stress and trauma occurred in patients with sole primary sites, leading to higher recurrence and mortality risk. Inconsistent with our results, however, was the report by Lv et al; 7 they assessed 142 Chinese AM patients and found that sites of lesion had no significant impact on overall survival (OS).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of ALM are diagnosed in the lower extremities, where most are located on the plantar sole and relatively few occur in the toenail apparatus. 5,13,[15][16][17] Conversely, most upper limb ALMs are associated with the fingernail apparatus. 13,17 There is conflicting evidence whether clinicopathologic variables differ between upper and lower limb ALM 18 and between nail and non-nail ALM.…”
Section: Introductionmentioning
confidence: 99%
“…The acral locations diagnosed with ALM have an interesting distribution. The majority of ALM are diagnosed in the lower extremities, where most are located on the plantar sole and relatively few occur in the toenail apparatus 5,13,15‐17 . Conversely, most upper limb ALMs are associated with the fingernail apparatus 13,17 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the low ORR after ICB therapy could be attributed to the modest response to the acral/mucosal subtype. In particular, acral melanoma is a skin malignancy with a low mutational burden that negatively influences the response to ICB therapy and results in poor prognosis relative to that of the other subtypes [ 4 - 6 , 16 , 17 ]. Furthermore, the incidence of the different subtypes of melanoma differs according to ethnicity.…”
Section: Discussionmentioning
confidence: 99%